Identification, Classification and Prioritization of Knowledge Sharing Techniques in Project Management Scope - Chaharsooghi Chaharsooghi; majid Hasani (Journal of Information Technology Management)
Management of project's knowledge is very effective in the performance of project management and carries a great portion in achieving the targets of organization and projects. In project-oriented organization, knowledge and experiences of projects play a crucial role. Accurate identification and suitable application of knowledge in success of knowledge management is necessary. This combines with accurate identification and suitable application of knowledge and knowledge sharing techniques and relationship between them. In this paper, recognition, prioritization and classification of knowledge and knowledge sharing techniques in project-oriented organization are taken to consideration with survey experts by the use of literature review, PMBOK, best statistic techniques and factor analysis. The results recommend that which kind of knowledge sharing technique groups is better for implementation by which kind of knowledge groups. Suitable application and accurate identification of knowledge and knowledge sharing techniques and relationship between them can play an effective role to perform knowledge management successfully in project management.